Effects of Salinity on Cadmium Availability in Soil And Fruits of Tomato (Lycopersicon Esculentum Miller) - Rahman, Md Moklesur; Bhuiyan, Mohammad Saiful Islam; Tareq, Shafi Mohammad (Bangladesh Journal of Botany, 2023)
Soil and water salinity are important problems in the coastal region of Bangladesh. Heavy metal also entering in the soil through various ways such as sewage sludge, fertilizers and pesticides. A pot experiment was conducted to study the variability of cadmium (Cd) availability in soil and tomato (Lycopersicon esculentum Miller) grown on to Cd-contaminated saline soil. The experiment was outlined in a completely randomized block design (RCBD) with a factorial layout which include 5 levels (0, 2, 4, 6 and 8 ds/m) of salinity and 4 levels (0, 10, 20 and 30 μg/g) of Cd. Result of soil analysis showed that the availability of Cd’s increased in soil with the increase of salinity level. Fruit analysis also showed that the concentration of Cd in tomato fruit increased with the increase of salinity, but the yield of tomato fruit decreased with the increase of salinity of the soil. Bangladesh J. Bot. 52(2): 315-321, 2023 (June)